Re-configuration of socio-political matrix from strategic planning experiences. comodoro rivadavia city case, argentina (2009)
In this article our principal objective is to deal with the transformations of the sociopolitical relational basis in Comodoro Rivadavia City towards the final years of the Twentieth century and the beginning of Twenty-first. The privatization of state’s companies during the ‘90s in the argentine Patagonia, and particularly, in Comodoro Rivadavia City, had a profound impact on the conformation of the sociopolitical relational basis in these societies. Since then, the successive local governments, realized about the imperious need of generating management procedure instruments that allow the local state and its respective community to foresee the orientation of public and private inversion. That is why, in three opportunities, the local government of Comodoro City undertook citizenship participation strategies with the objective of approaching to a strategic planification process of regional and local territorial development. These kind of politic-institutional spaces open a great opportunity to observe how, in a given society, the local state, the political regime and the socioeconomic and cultural basis link each other.